Investigação das propriedades de medida do teste Timed “Up and Go” Assessment of Biomechanical Strategies (TUG-ABS) para crianças e adolescentes com paralisia cerebral - Silva, Ana Paula Zanardi da (2024)
Changes in mobility are important activity limitations in individuals with cerebral palsy (CP). One of the assessment instruments frequently used to measure your mobility is the Timed “Up and Go” (TUG). Aiming to offer more planned information about the biomechanical strategies used to perform the test, the Timed “Up and Go” Assessment of Biomechanical Strategies (TUG-ABS) was developed, which has not yet been validated for children and adolescents. Objectives: To investigate the measurement properties (validity and reliability) of the TUG-ABS test for children and adolescents with CP. Methodology: This is a methodological study, in which nine professionals answered a questionnaire with questions to determine content validity and 50 participants with CP (levels I to III in the gross motor function classification system [GMFCS]) and 50 participants typically developing (TD), aged 7 to 18 years, performed the TUG test to determine the discriminant and convergent validity and reliability of the TUG-ABS. The test was filmed with a video camera positioned in the sagittal plane for subsequent TUG-ABS scoring. For content validity, the analysis of discursive responses was carried out descriptively and of multiple choice responses using the content validity index per item (I-IVC). To compare groups in TUG-ABS phases and total victories, Mann-Whitney tests were applied. Spearman brightness coefficients determined the associations between phase predictions and total TUG-ABS results and the time taken to perform the TUG. The inter-rater reliability of stage wins and total scores was calculated using the weighted Kappa statistic. Results: The TUG-ABS presented adequate content validity from the perspective of professionals and all questions met or exceeded the I-IVC of 0.78. It was able to differentiate between children and adolescents with CP and TD and presented a negative impact on the time taken to perform the TUG in the group with CP. Furthermore, it presented adequate inter-rater reliability. Conclusion: The TUG-ABS declared adequate measurement properties in children and adolescents with CP.